2018
DOI: 10.1194/jlr.s087163
|View full text |Cite
|
Sign up to set email alerts
|

MS-based lipidomics of human blood plasma: a community-initiated position paper to develop accepted guidelines

Abstract: Human blood is a self-regenerating lipid-rich biological fluid that is routinely collected in hospital settings. The inventory of lipid molecules found in blood plasma (plasma lipidome) offers insights into individual metabolism and physiology in health and disease. Disturbances in the plasma lipidome also occur in conditions that are not directly linked to lipid metabolism; therefore, plasma lipidomics based on MS is an emerging tool in an array of clinical diagnostics and disease management. However, challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(241 citation statements)
references
References 133 publications
(137 reference statements)
6
227
0
1
Order By: Relevance
“…In this regard, several invivo models have been established to study the pathogenesis of this metabolic syndrome, and there are significant experimental evidences that shows impaired lipid metabolism plays a crucial role therein 12,13 . Many studies were conducted the analysis at genomic 14 and proteomic level 15 And recently developed MS-based lipidomic techniques show a high intricacy of the many circulating plasma lipidome 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several invivo models have been established to study the pathogenesis of this metabolic syndrome, and there are significant experimental evidences that shows impaired lipid metabolism plays a crucial role therein 12,13 . Many studies were conducted the analysis at genomic 14 and proteomic level 15 And recently developed MS-based lipidomic techniques show a high intricacy of the many circulating plasma lipidome 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Validation of the novel method demonstrated its suitability for large-scale studies despite the higher variations observed for some samples. These variations are related to inhomogeneity of samples and lipolytic activity that requires further investigations considering pre-analytical issues as an essential part of lipidomic workflows and their standardization [29,30,41]. Therefore, we recommend performing measurements in triplicate, when high accuracy is needed.…”
Section: Resultsmentioning
confidence: 99%
“…IS compounds are critical for LC-MS-based quantitation (24). Stable isotopically labeled analogs are desirable as IS compounds because these nonnatural compounds can be quantified without any signal overlap with natural compounds, and such standards can properly compensate for variability in sample extraction and LC-MS analysis.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Because both acyl chain length and retention time of D 31 -16:0-CoA are close to those of 17:0-CoA rather than 26:0-CoA, these results indicate that the amounts of VLCFA-CoA species with fewer number of double bonds in their acyl chain moiety were underestimated in this study, and the amount of 26:1-CoA may be much higher than that of 18:1-CoA in both X-ALD fibroblasts and ABCD1-deficient HeLa cells. The ionization efficiency can be influenced by ion suppression or ion enhancement depending on the mobile phase conditions and the presence of coeluting compounds (24), and it is desirable to prepare an IS compound for each acyl-CoA species for absolute quantitation. If stable isotopically labeled CoA is abundantly available, the preparation of each IS compound may be facilitated by a condensation reaction between each nonlabeled FA and the labeled CoA as conducted in this study.…”
Section: Downloaded Frommentioning
confidence: 99%